Training Public Service Interpreters in the UK: A fine balancing Act - de Pedro Ricoy, Raquel (The Journal of Specialised Translation, 2010)
The training of public service interpreters is a very complex endeavour that must balance pedagogical considerations and market requirements. This paper considers the interrelationship between academic programmes, qualifications, curriculum design and standards in the field of public service interpreting (PSI) in connection with the perceived status of the profession and the desirability of regulated monitoring practices, whilst not losing sight of the constraints imposed by socio-economic circumstances. The desirability of conducting extensive empirical research into the needs of public service agencies and PSI providers alike, as well as into the profile of interpreters, is also emphasised, in an attempt to match training provision and community needs in a multicultural, multilingual context. It can be concluded that a coherent, integrated approach to training, practice and quality assurance will result in an enhanced status of the PSI profession, which can only be beneficial to society at large